Deformity Reconstruction Surgery for Blount’s Disease - Craig A. Robbins (Children, 2021)
Blount’s disease is an idiopathic developmental abnormality affecting the medial proximal tibia physis resulting in a multi-planar deformity with pronounced tibia varus. A single cause is unknown, and it is currently thought to result from a multifactorial combination of hereditary, mechanical, and developmental factors. Relationships with vitamin D deficiency, early walking, and obesity have been documented. Regardless of the etiology, the clinical and radiographic findings are consistent within the two main groups. Early-onset Blount’s disease is often bilateral and affects children in the first few years of life. Late-onset Blount’s disease is often unilateral and can be sub-categorized as juvenile tibia vara (ages 4–10), and adolescent tibia vara (ages 11 and older). Early-onset Blount’s disease progresses to more severe deformities, including depression of the medial tibial plateau. Additional deformities in both groups include proximal tibial procurvatum, internal tibial torsion, and limb length discrepancy. Compensatory deformities in the distal femur and distal tibia may occur. When non-operative treatment fails the deformities progress through skeletal maturity and can result in pain, gait abnormalities, premature medial compartment knee arthritis, and limb length discrepancy. Surgical options depend on the patient’s age, weight, extent of physeal involvement, severity, and number of deformities. They include growth modulation procedures such as guided growth for gradual correction with hemi-epiphysiodesis and physeal closure to prevent recurrence and equalize limb lengths, physeal bar resection, physeal distraction, osteotomies with acute correction and stabilization, gradual correction with multi-planar dynamic external fixation, and various combinations of all modalities. The goals of surgery are to restore normal joint and limb alignment, equalize limb lengths at skeletal maturity, and prevent recurrence. The purpose of this literature review is to delineate basic concepts and reconstructive surgical treatment strategies for patients with Blount’s disease.